The Effectiveness of Project-Based Learning (PjBL) on Learning Outcomes: A Meta-Analysis Using JASP - Fadhilah Fadhilah; Muhammad Husin; Rian Fadia Raddhin (JIPF (Jurnal Ilmu Pendidikan Fisika), 2023)
This study aims to analyze the effectiveness of the effect of the Project-Based Learning (PjBL) learning model on student learning outcomes. There were 26 articles analyzed in this study. The articles collected have been published in national journals, international conferences, and international journals for the last 3 years from 2018 to 2021 related to Project-Based Learning (PjBL) and learning outcomes. This research uses a meta-analysis method by calculating the effect size value in each article. Four formulas are used to calculate the effect size value for each article. This research is meta-analysis research based on the form of learning outcomes with the Project-Based Learning (PjBL) model, Year, Type of Integration, Effect Size Value, and Type of Publication. The meta-analysis results show that the average effect size of PjBL on student learning outcomes is high and significant. The Project-Based Learning (PjBL) model is mostly integrated with the Conventional Learning (CvL) model. The order of most publications starts from national journals, international journals, and international conferences, all three of which have an average effect size value in the high category, and there is no publication bias. Based on data analysis, Project-Based Learning (PjBL) can increase students' creativity in learning. Besides, it helps students to be able to think more critically in solving problems. This model can also improve students' skills to help them compete in the 21st century and the era of society 5.0.